2020
DOI: 10.3389/fpsyg.2020.566199
|View full text |Cite
|
Sign up to set email alerts
|

Caring for Coronavirus Healthcare Workers: Lessons Learned From Long-Term Monitoring of Military Peacekeepers

Abstract: Background: The current outbreak of the coronavirus disease (COVID-19) is of unprecedented proportions in several regards. Recent reports suggest that many frontline healthcare workers (HCWs) suffer from mental health problems, including posttraumatic stress symptoms (PTSS). Previous studies have identified several key factors associated with short-term PTSS in pandemic HCWs, yet limited data is available on factors associated with long-term PTSS. Understanding the psychological impact of the pandemic on HCWs … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 65 publications
(71 reference statements)
0
8
0
Order By: Relevance
“…The correlations between cumulative exposure to military trauma, morally conflictual experiences and resulting presence of psychopathology, even after a span of three decades post-deployment, were notably significant. Indeed, figures in the current cohort (Gjerstad, Bøe, Falkum, Martinsen, et al, 2020 ; Gjerstad, Bøe, Falkum, Nordstrand, et al, 2020 ) indicated a greater prevalence of PTSD amongst peacekeeper veterans than those previously reported in short term studies of this population group (Forbes et al, 2016 ; Maguen et al, 2004 ). The current sample reported similar levels of self and other perpetrated PMIEs to those reported in American combat samples (Jordan et al, 2017 ).…”
Section: Discussionmentioning
confidence: 55%
“…The correlations between cumulative exposure to military trauma, morally conflictual experiences and resulting presence of psychopathology, even after a span of three decades post-deployment, were notably significant. Indeed, figures in the current cohort (Gjerstad, Bøe, Falkum, Martinsen, et al, 2020 ; Gjerstad, Bøe, Falkum, Nordstrand, et al, 2020 ) indicated a greater prevalence of PTSD amongst peacekeeper veterans than those previously reported in short term studies of this population group (Forbes et al, 2016 ; Maguen et al, 2004 ). The current sample reported similar levels of self and other perpetrated PMIEs to those reported in American combat samples (Jordan et al, 2017 ).…”
Section: Discussionmentioning
confidence: 55%
“…From a clinical perspective, all these findings support the relevance of developing targeted interventions to protect HCWs' mental health because, as evidenced by the literature [53,54], poor mental health due to the impact of the pandemic might affect the quality of care provided by HCWs, and could lead to long-term psychological difficulties. These considerations are strengthened by the results of an interesting study [37] where mental health professionals (MHPs) reported better overall mental health and lower post-traumatic symptoms than the symptoms observed in other kinds of HCWs during the pandemic.…”
Section: Discussionmentioning
confidence: 56%
“…Totally 47 articles reported mental health problems, including PTSD [ 13 15 , 17 24 , 26 37 ], stress [ 38 45 ], anxiety and depression [ 35 , 39 , 46 – 60 , 62 , 63 ], and psychiatric disorders [ 13 , 33 , 46 ]. PTSD: Two studies reported the high prevalence of PTSD and symptoms among UN peacekeepers [ 13 , 14 ], ranging from about 5to 20% in a short time after service.…”
Section: Resultsmentioning
confidence: 99%
“… Region of the Americas: Brazil, U.S. Haiti, Kosovo, Bosnia Questionnaire, Cohort study Social environmental factors (work-to-family enrichment support, family stressors and financial difficulties, differences in support structures). Psychological factors Bramsen et al 2000 [ 15 ], Dirkzwager et al 2005 [ 124 ], Ippolito et al 2005 [ 47 ], Maguen et al 2006 [ 121 ], Souza et al 2008 [ 24 ], Jia et al 2009 [ 49 ], Proctor et al 2009 [ 125 ], Shao et al 2011 [ 53 ], Britt et al 2011 [ 42 ], Orme et al 2014 [ 128 ], Silva et al 2015 [ 129 ], Zhou et al 2016 [ 104 ], Lamb et al 2018 [ 126 ], Zhao et al 2019 [ 62 ], Gjerstad et al 2020 [ 37 ] Western Pacific Region: China, Australia Timor-Leste or the Solomon Islands, The Democratic Republic of the Congo, Lebanon, Multination Questionnaire, Retrospective study Psychological factors (higher hardiness scores are associated with lower levels of reported psychological distress and physical ill-health, resilience, life stress events and emotional experiences, lack of patience, loss of emotional control, longing for family members, instability state of mind). European Region: Netherlands, Norway, U.K. Lebanon, Yugosla, Multination Cross-sectional study, Questionnaire, Interview Psychological factors (personal barriers to disclose experiences and current unemployment, vulnerabilities and exposure to traumatic events, confidence and team cohesiveness to build personnel’s resilience).…”
Section: Methodsmentioning
confidence: 99%